“The Capitalist Lie”: A Postcolonial, Marxist Analysis of The Extreme Centre - Hammad Mushtaq; Nighat Ahmad (NUST Journal of Social Sciences and Humanities, 2021)
This research presents a postcolonial analysis of Tariq Ali’s non-fictional work. The ‘Extreme Centre’ focusing mainly on the Marxist and Althusserian theoretical perspectives of the self and the other. The notions of Marxist social divide between the bourgeoisie and the proletarians, and the Althusser’s Ideology and Ideological State Apparatuses have been applied to decipher Tariq Ali’s standing as a postcolonial writer. The strong impact of the imperial and neo-imperial Ideology has been influencing the subjectivities of the masses around the world, including the masses in the West through the spread of imperial and neo-imperial Ideology. The interpellated subjectivities of the western proletarians are constructed by making them believe that the Western ideological and physical supremacy over the world would herald a golden age. However, the illusion of growth, opulence, and liberty is blemished by the outcomes of the imperial wars and capitalist greed. A critical reading of Ali’s work reveals that heralding of a Global revolution is indispensable yet not imminent, until the initiation of dissent from within the Empire.